Optimal combination of wage cuts and layoffs-the unexpected side effect of a performance-based payment system - Izumi Yokoyama; Takuya Obara (IZA Journal of Labor Policy, 2017)
This study analyzes the trade-off relationship between layoffs and wage cuts. If the introduction of a performance-based payment system stimulates workers' pecuniarymotivated minds, their morale can be damaged more severely by wage cuts than prior to the introduction thereof. Utilizing this idea, we demonstrate theoretically that the more heavily wages are based on performance, the more firms, fearing that workers' morale will be damaged by wage cuts, try to avoid wage cuts and instead prefer layoffs. Next, we show empirically the trend whereby firms with performance-based payment systems are unlikely to implement wage cuts. Given this first-stage regression, the status of a performance-based payment system, based on the firm's past decision and assured to be exogenous, is employed as an instrumental variable (IV) for wage cuts in a layoff regression model to overcome simultaneous bias. In the second-stage regression, the IV estimates for the impact of wage cuts on layoffs are significantly negative: if a firm implements wage cuts, it will reduce the probability of layoffs by 0.172. This supports the theoretical implication that implementing wage cuts can be a potential device for reducing layoffs. These results may imply an unexpected side effect of the increasing use of performance-based payment systems: as such systems become more widespread, layoffs will increase because firms will become less likely to impose wage cuts, thus potentially resulting in high unemployment.
Keywords: J30; J33; J63; 330; Layoff; Wage cut; Morale; Performance-based payment system